Twin-twin Transfusion Syndrome with a Single Ectopic Kidney in a Twin Donor. Case Presentation - Gerardo Rogelio Robaina Castellanos; Solangel de la Caridad Riesgo Rodríguez; Esther María Tristá Ricardo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Twin-twin Transfusion Syndrome presents more frequently in diamniotic monochromic twins. In advanced stages and without prenatal intervention, is associated to high rates of peri natal mortality and neurological sequel in the survivors. It is presented a case of a pair of twins with severe depression at birth in which it was diagnosed a Twin-twin Transfusion Syndrome, later confirmed with the presence of anemia in the donor twin and polycythemia in the receptor twin. Both twins had an unfavourable evolution with an early neonatal death. Necropsy findings were comparable with secondary damage to the syndrome, with the particularity that both had evidences of pulmonary infection and a renal malformation in the donor twin which is not included in the proper malformations of this syndrome. The objective of this work is to point out the essential elements for the diagnosis and antenatal treatment for this disease through the peculiarities of the presented case.